Phosphate removal from water using a hybrid material in a fixed-bed column (2018)
In this study, the removal and recovery of phosphorus (P) were evaluated on fixed-bed column systems using a hybrid adsorbent, i.e. HFeO. The effect of flow rates (1.0–2.5 mL/min) and bed heights (2–6 cm) was examined, and the experimental data were adjusted to the Thomas, Adams–Bohart and Yoon–Nelson models. The results indicate that for the flow rate of 1.0 mL/min and bed height of 2 cm, a maximum adsorption capacity of P (qTh) of 53.57 mg/g is obtained. 6% NaCl acts as the best eluting agent with a 97% efficiency of P desorption. Finally, it was found that HFeO is able to support up to three cycles of adsorption–desorption, decreasing its capacity of P adsorption by 26% with respect to the initial capacity. © 2018 Elsevier Ltd